Characteristic of the rare pathogen of onychomycosis Phoma macrostoma (sin. Didymella macrostoma) (Experimental biology, 2020)
The article presents the results of studying the biological properties of the Phoma macrostomastrain, first described in Kazakhstan as the causative agent of onychomycosis. The authors obtained a pure culture of Phoma macrostoma coelomic, isolated from the affected nail plate of a patient in a narcological dispensary, and studied its biological properties: cultural, morphological, biochemical. Surface cultivation on differential media, microscopy in agar blocks and adhesive tape preparations, molecular genetic identification was carried out. The features of the formation of  fungus colony are described, the characteristic morphological structures of the coelomycete, moderate fermentation of carbohydrates and the absence of urease activity are revealed. On the dextrose agar of Sabouraud nutrient medium, by 10-18 days, flat colonies of pale pink colour, with a pinkish-orange tint in the centre, yellowish along the edge, with a raised centre and relief radial stripes, were formed, the reverser was yellow-brown. The appearance of single growth tubes was noted within the first 12 hours, the massive division of single cells and the growth of filamentous filaments - 18 hours after sowing the spores. By the end of the second day, there is a powerful growth and active branching of the mycelium, the appearance of rudiments of pycnidia in the form of seals along the course of mature mycelial filaments, by the end of the third day, the formation of pycnidia and chlamydospores of the brown colour of various shades. Ripe transparent, unicellular, elliptical pycnospores emerge from pycnidia and  located in the form of a mucous drop. The strain is characterized by moderate saccharolytic activity in relation to glucose, sucrose, mannose, mannitol, lactose, the almost complete absence of urease activity. Molecular genetic identification by the Sanger method made it possible to identify the Phoma macrostoma strain with 100% certainty and to deposit the nucleotide sequence in GenBank as isolate No. MN701978.1 Didymella macrostoma 104-Kz.Key words: biology of the pathogen, genetic identification, onychomycosis, pycnidia, coelomycetes